2018
DOI: 10.1155/2018/2094621
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice on Hygiene and Morbidity Status among Tertiary Students: The Case of Kotebe Metropolitan University, Addis Ababa, Ethiopia

Abstract: Considerable fractions of the world's diseases are communicable, of which over 60% are infectious. Knowledge, attitude, and practice of hygiene are very important to decrease these disease burdens especially in places like higher education institutions. This study is aimed at revealing the status and gaps on knowledge, attitude, and practice of hygiene among Kotebe Metropolitan University students. Alongside, morbidity records of the students' clinic are reviewed. Sampled regular students who are boarding and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…The present study revealed that 25.7% and 1.6% of participants were “sometimes” washing their hands before eating and after defecation, respectively. The study conducted in Addis Ababa, Ethiopia showed that 17.1% and 14.4% do not practice hand washing before meals and after defecation, respectively [26] . Moreover, a significant number of respondents answered that washing fruits before eating, eating food outside the home, and cutting nails were being done “sometimes”.…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed that 25.7% and 1.6% of participants were “sometimes” washing their hands before eating and after defecation, respectively. The study conducted in Addis Ababa, Ethiopia showed that 17.1% and 14.4% do not practice hand washing before meals and after defecation, respectively [26] . Moreover, a significant number of respondents answered that washing fruits before eating, eating food outside the home, and cutting nails were being done “sometimes”.…”
Section: Discussionmentioning
confidence: 99%
“…Besides teachers, parents, and classmates' attitudes significantly influence handwashing and hygiene behaviours and habits among students [ 15 17 ]. Nevertheless, students' hygiene knowledge, attitudes, and practices have shown significant discrepancies between genders [ 18 ]. It has been found that the interventions of handwashing and personal hygiene in school children have led to a significant reduction in diarrhoea cases and absence rates among students [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia these diseases account for 80% of the illnesses together with other infectious diseases and malnutrition. 14 Food handlers with poor personal hygiene and lack of awareness of important issues in preventing foodborne diseases, working in food establishments could be potential sources of infections of many intestinal helminthes of protozoa and estrogenic pathogens. 15 Institutional foodservice is an important sector of the food industry.…”
Section: Introductionmentioning
confidence: 99%